Trade-Offs in Phosphorus Acquisition Strategies of Five Common Tree Species in a Tropical Forest of Puerto Rico - Yaffar, Daniela; Defrenne, Camille E.; Cabugao, Kristine G.; Kivlin, Stephanie N.; Childs, Joanne; Carvajal, Niko; Norby, Richard J. (Frontiers in Forests and Global Change, 2021)
Tree species that are successful in tropical lowlands have different acquisition strategies to overcome soil phosphorus (P) limitations. Some of these strategies belowground include adjustments in fine-root traits such as morphology, architecture, association with arbuscular mycorrhizal fungi, and phosphatase activity. Trade-offs among P-acquisition strategies are expected because of their respective carbon cost. However, empirical evidence remains scarce which hinder our understanding of soil P-acquisition processes in tropical forests. Here, we measured seven fine-root functional traits related to P acquisition of five common tree species in three sites of the Luquillo Experimental Forest in Puerto Rico. We then described species-specific P-acquisition strategies and explored the changes in fine-root trait expression from 6 months before to 6 months after two consecutive hurricanes, Irma and María, passed over the island. We found that variations in root trait expression were driven mainly by the large interspecific differences across the three selected sites. In addition, we revealed a trade-off between highly-colonized fine roots with high phosphatase activity and fine roots that have a high degree of branching. Furthermore, the former strategy was adopted by pioneer species (Spathodea campanulata and Cecropia schreberiana), whereas the latter was adopted by non-pioneer species (mostly Dacryodes excelsa and Prestoea montana). Additionally, we found that root trait expression did not change comparing 6 months before and after the hurricanes, with the exception of root phosphatase activity. Altogether, our results suggest a combination of structural and physiological root traits for soil P acquisition in P-poor tropical soils by common tropical tree species, and show stability on most of the root trait expression after hurricane disturbances.